Risk communication: ethics, psychology, law - E. O. Taratukhin (Российский кардиологический журнал, 2021)
When communicating with a patient, a doctor is within a certain cultural practice (science-based medicine and state health care system), falling outside the limits of which is not legal. However, a broader understanding of medicine as a cultural phenomenon with a focus on health also requires a more varied perspective on patient care. The patient’s problem can be more complex than looking at it from science- and evidence-based point of view. Therefore, in risk communication as an element of work with adherence or as part of signing informed consent, different ways are needed to consider a patient’s situation. An ethical and psychological perspective on clinical interactions allows for a more holistic view of the disease.